Assédio sexual: prevalência e consequências em trabalhadoras do varejo formal na cidade de São Luís do Maranhão - COSTA, Ana Clara Dos Santos (2022)
Violence against women multiplies in various spaces, from domestic to public, and this violation of conduct can be present in the organizational environment, in the form of sexual harassment, bringing professional, physical and emotional damages, such as postpartum stress disorder. traumatic. And companies can have negative consequences in the relational, productive and financial areas. Harassment can be divided into three dimensions: Gender Harassment, Unwanted Sexual Attention and Sexual Coercion. Considering the importance of the phenomenon, the objectives of the study are to investigate the prevalence of sexual harassment in 125 workers in the retail segment who work in establishments of the commercial conglomerate "Rua Grande", located in the Centro neighborhood, in São Luís do Maranhão. The research design is of the Survey type, with a non-probabilistic convenience sample to identify the profile of the harassed and the psychological consequences. As an instrument, the Sexual Harassment Questionnaire (QAS) was first used to measure the frequency of harassment. If the participants confirmed any item of harassment, they answered a structured interview to contextualize this episode and the Post Traumatic Stress Disorder (PTSD) Scale to investigate the development of these symptoms. Data collection took place before and/or after business hours. To analyze the quantitative results, JASP statistical software (v. 0.13.1.0) was used in order to project data regarding the three dimensions of harassment, correlating with the variables: age, marital status, length of service and harassment scores with PTSD. The results showed that 35,2% (n=44) suffered harassment and from this subgroup 72,7% (n=32) did not perceive this behavior, while 27,3% (n=12) recognized it. A moderate positive correlation was identified between sexual harassment and post-traumatic stress disorder and the variable length of service with the frequency of harassment. The variable “marital status” did not show significant differences in harassment between married and single women. Men were the main harassers. However, the reports had a female perspective. Participants who work in companies with more employees, the majority being men, reported more instances of harassment. It is hoped to have collaborated with national statistics on sexual harassment, which are still scarce, and to provide information to subsidize organizational managers and public agents for the identification, prevention, treatment of these occurrences and their victims.